Impact of periodontitis on gingival crevicular fluid miRNAs profiles associated with cardiovascular disease risk - Isola, Gaetano; Santonocito, Simona; Distefano, Alfio; Polizzi, Alessandro; Vaccaro, Manuel; Raciti, Giuseppina; Alibrandi, Angela; Li Volti, Giovanni (Journal of periodontal research, 2023)
Background and Objective Recent emerging evidence has shown that microRNA (miRNAs) is involved in several epigenetic processes linked with periodontitis, increased oxidative stress and cardiovascular disease (CVD). The present study aimed to assess the impact of periodontitis on gingival crevicular fluid (GCF) miRNAs expression associated with CVD risk and to evaluate possible confounders that influenced this association. Materials and Methods For the present study, healthy controls (n = 28) and subjects with CVD (n = 28), periodontitis (n = 30) and periodontitis + CVD (n = 29) were enrolled. All subjects underwent regular periodontal examinations and blood sampling. In addition, GCF sampling was performed, and miRNAs 7a‐5p, 21‐3p, 21‐5p, 100‐5p, 125‐5p, 200b‐3p, and 200b‐5p expression was analyzed using a real‐time quantitative polymerase chain reaction (RT‐PCR). Results The results showed that periodontitis and periodontitis + CVD subjects presented significantly different GCF miRNAs expression compared to healthy controls and CVD subjects. More specifically, compared to healthy controls and CVD, subjects with periodontitis and periodontitis + CVD showed higher GCF miRNA 7a‐5p, miRNA 21‐3p, miRNA 21‐5p, miRNA 200b‐3p, and miRNA 200b‐5p (p < .05) and lower miRNA 100‐5p, miRNA 125‐5p levels (p < .05). Furthermore, the multivariate regression analysis evidenced that periodontitis (miRNA 21‐3p, 100‐5p) and periodontal inflamed surface area (PISA) (miRNA 7a‐5p, 21‐3p, 21‐5p, 100‐5p, 125‐5p, 200b‐3p) were significant predictors of GCF miRNAs concentration (p < .05). Conclusion The results of the study highlighted that the periodontitis and periodontitis + CVD group showed higher GCF miRNAs expression than healthy controls and CVD subjects. Furthermore, periodontitis and its extent (PISA) were revealed as significant predictors of GCF miRNAs associated with CVD risk.